Integrity verification protocol based on privacy homomorphism data aggregation - Xing LI; Chun-yan LI; Liang-min WANG (Tongxin xuebao)
Secure data aggregation in wireless sensor networks can effectively prevent privacy leakage,data tampering and other issues,it also achieves efficient data transmission.An integrity verification protocol based on privacy homomorphism data aggregation (IV-PHDA) was presented.The protocol uses homomorphism encryption to ensure data privacy,then it used random detection nodes to detect the integrity of the aggregated results to verify whether the aggregation node faithfully transmit each data packet.The theoretical analysis and simulation comparison verify the performance of the algorithm,the results show that this protocol can detect data integrity through transmission,and achieve better privacy protection and higher data accuracy.